(untitled) (Journal of Pakistan Orthopaedic Association, 2015)
Objective: To evaluate the outcome of the Ilizarov technique in open fractures and nonunion of the femur. Material and Method: This multicenter case series study was performed on 27 consecutive patients at Orthopedic Unitsof Khyber Girls Medical College, Postgraduate Medical Institute Hayatabad Medical Complex and Akbar Medical Center Peshawar from January 2012 to February 2015. Patients of both gender with age between 15 to 72 years, having fresh open fractures and nonunion (clean and infected nonunion) in femur were included in the study. Ilizarov fixator of hybrid type were used in all cases. Bone healing and the functional results were assessed according to criteria given by ASAMI (Association for the study and application of the method of Ilizarov). Results: Out of 27 patients, 19 (70.4%) were male and 08(29.6%) were female. Mean age was 40 years. Thirteen(48.1%) patients had infected non-union 04 (14.8%) aseptic non union and 10(37%) were fresh open fractures. Segment Transport was done in 13(48.1%) patients while compression/distraction was done in 20(74.1%) patients. Bone result was excellent in 14 (51.9%), good in 08 (29.6%) and fair in 05 (18.5%)patients while functional results were excellent in 8 (29.6%), good in 11 (40.7%), fair in 06 (22.2%) and poor in 02 (7.4%) patients. Conclusion: Ilizarov ring fixator is excellent treatment modality for femoral non-union with a defect, regarding bone union, deformity correction, infection eradication, limb length achievement and limb function